EFEKTIVITAS PELESTARIAN DAN PENGEMBANGAN KESENIAN DAN KEBUDAYAAN DAERAH (JAWA) MELALUI MEDIA TELEVISI LOKAL Ã¢â‚¬Å“JOGJA TVÃ¢â‚¬ YOGYAKARTA - DA, NRA. Candra (Seni Media Rekam ISI Surakarta, 2010)
Local television station as one form of public broadcast media have the same role in organizing the national private television broadcasts, such as in Jakarta. Although the majority of the material broadcast was inspired by various aspects of life in the area, sometimes some of the programs broadcast before it is seeded and got a good response and interest by the audience watching it. One example is a special broadcast program material lifting of traditional art forms and cultures that are sometimes presented with a more varied format. Such as local television, Jogja TV, has now become an expectation, especially for people who are in the range of broadcasting (public areas) as one of the effective media to contribute to developing the arts and culture while preserving valuable areas of Yogyakarta (Java). As a Special Region is expected to achieve a dynamic society and high culture, so as to develop the basis that there is a tradition of innovation in all spheres of social life of art and culture, economics, and science and technology as a form of community life in dynamic city as YogyakartaKeywords: local art, local culture, preservation and development, local television, Jogja TV.